Tipologi Relasi Gereja dan Pemerintah Menurut Philip J. Wogaman: Konstruksi Teologi Publik Perspektif Pentakostal di Indonesia - Hasiholan, Anggi Maringan; Siahaan, Harls Evan R. (STT Iman Jakarta, 2024)
The typology of church and government relations proposed by Philip J. Wogaman provides a conceptual framework for understanding the levels of church engagement in the public sphere. This study explores how Pentecostal communities in Indonesia can actively participate in the socio-political arena without losing their theological identity. Through the seven levels of participation, the church can influence societal ethos, educate congregations, and even take more radical steps, such as civil disobedience. However, political neutrality for the sake of peace is not included in the levels of participation outlined by Wogaman. By integrating pneumatological values and public theology principles, Pentecostal churches hold significant potential to become social and spiritual transformation agents, addressing the challenges of religious pluralism, poverty, and social injustice in Indonesia. Abstrak Tipologi relasi gereja dan pemerintah menurut Philip J. Wogaman memberikan kerangka konseptual untuk memahami level keterlibatan gereja dalam ruang publik. Penelitian ini membahas bagaimana komunitas Pentakostal di Indonesia dapat berperan aktif dalam ranah sosial-politik tanpa kehilangan identitas teologisnya. Melalui tujuh tipologi partisipasi, gereja dapat memengaruhi etos masyarakat, mendidik jemaat, hingga mengambil langkah-langkah yang lebih radikal seperti pembangkangan sosial. Namun, netralitas politik demi perdamaian tidak termasuk dalam kategori partisipasi yang disebutkan oleh Wogaman. Dengan pendekatan yang mengintegrasikan nilai pneumatologis dan prinsip teologi publik, gereja Pentakostal memiliki potensi besar untuk menjadi agen transformasi sosial dan spiritual, menjawab tantangan pluralisme agama, kemiskinan, dan ketidakadilan sosial di Indonesia.